2011
DOI: 10.1016/j.vaccine.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Development of dengue DNA vaccines

Abstract: a b s t r a c tVaccination with plasmid DNA against infectious pathogens including dengue is an active area of investigation. By design, DNA vaccines are able to elicit both antibody responses and cellular immune responses capable of mediating long-term protection. Great technical improvements have been made in dengue DNA vaccine constructs and trials are underway to study these in the clinic. The scope of this review is to highlight the rich history of this vaccine platform and the work in dengue DNA vaccines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
(33 reference statements)
0
37
0
1
Order By: Relevance
“…Although there are a number of studies describing DNA vaccines against dengue Azevedo et al, 2011;Galula et al, 2014;Khanam et al, 2006;Konishi et al, 2006;Ocazionez Jimenez & Lopes da Fonseca, 2000;Prompetchara et al, 2014;Ramanathan et al, 2009;Raviprakash et al, 2001Raviprakash et al, , 2006, to date there has been only one human clinical trial for a dengue DNA vaccine involving a Phase 1 study of a plasmid expressing the PrM and E proteins of DENV1 . In all cases, these vaccines have been proved to be safe and well-tolerated in humans, although low immunogenicity is still a concern associated with genetic vaccines in general (Coban et al, 2011;Danko et al, 2011). DNA immunization with constructs displaying the same antigenic determinants but different secretory capacity allowed us to demonstrate that antigen secretion is indeed an important characteristic to take into consideration for the design of efficient genetic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a number of studies describing DNA vaccines against dengue Azevedo et al, 2011;Galula et al, 2014;Khanam et al, 2006;Konishi et al, 2006;Ocazionez Jimenez & Lopes da Fonseca, 2000;Prompetchara et al, 2014;Ramanathan et al, 2009;Raviprakash et al, 2001Raviprakash et al, , 2006, to date there has been only one human clinical trial for a dengue DNA vaccine involving a Phase 1 study of a plasmid expressing the PrM and E proteins of DENV1 . In all cases, these vaccines have been proved to be safe and well-tolerated in humans, although low immunogenicity is still a concern associated with genetic vaccines in general (Coban et al, 2011;Danko et al, 2011). DNA immunization with constructs displaying the same antigenic determinants but different secretory capacity allowed us to demonstrate that antigen secretion is indeed an important characteristic to take into consideration for the design of efficient genetic vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of recently published phase IIb/III trials conducted in five Asian countries in which dengue is endemic, the Sanofi-Aventis chimeric yellow fever (YF) 17D-DENV-1 to -4 CYD tetravalent dengue vaccine (TDV) showed an acceptable safety profile and 56% overall efficacy (4); however, the vaccine failed to confer significant protection against DENV-2 (5). These findings underscore the need for the development of alternative vaccine platforms, such as those based on purified inactivated virus (6), DNA (7), and recombinant subunit truncated envelope (E) proteins (e.g., 80% envelope protein [80E]) (8). Some of these alternative vaccine candidates have been evaluated in phase I trials, where they were found to be safe and immunogenic while allowing for much shorter immunization regimens.…”
mentioning
confidence: 99%
“…Although DNA vaccine are easy to manufacture and maintain however weak immunogenicity should be addressed. This can be achieved by addition of adjuvants or increasing the expression of immunogenic proteins [45]. With the development of efficient promotors and constructs and delivery mechanisms DNA vaccine will be an important tool in modern world of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Both Intradermal and intramuscular route of DNA vaccine administration were employed; it was observed that intradermal immunization produces less immunogenic response than intramuscular immunization in rhesus monkeys. In another trial Konishi et al [44] PrM and E genes of Guinea C strain of DENV-2 produced neutralizing antibodies and anamnestic response in immunized mice [45].…”
Section: Dna Vaccines Against Denvmentioning
confidence: 99%